The Role of the Penderes Foreman on Work Productivity at PT. Bridgestone - Ramadani, Khairunisa; Salianto; Hasanah , Nurul; Saragih , Tarisa Nazlita; Anggraini , Yunita (CV. Generasi Insan Rafflesia, 2023)
In an organization, a leader who has the soul of a leader is needed in the success of achieving the expected goals in an organization. The foreman has the job of leading and supervising the work carried out by workers. This study was conducted to determine the role of the crane foreman on work productivity at PT. Bridgestone. The type of research conducted was a qualitative research design. Data collection techniques used interviews between researchers and informants/source persons from related parties. Based on the results of the research, it was found that the crane foreman's work can be said to be all related to the crane, both safety and health, attitude and behavior, work environment and the output produced by the crane. The conclusion obtained is that the work of the tapper is the responsibility of the foreman. Usually the foreman provides motivation, safety briefing, good communication, supervision, evaluation, and can solve problems.